Heat-processed Panax ginseng and diabetic renal damage: active components and action mechanism - Kang, Ki Sung; Ham, Jungyeob; Kim, Young-Joo; Park, Jeong Hill; Cho, Eun-Ju; Yamabe, Noriko (KOREAN SOC GINSENG, 2013)
Diabetic nephropathy is one of the serious complications in patients with either type 1 or 2 diabetes mellitus but current treatments remain unsatisfactory. Results of clinical research studies demonstrate that Panax ginseng can help adjust blood pressure and reduce blood sugar and may be advantageous in the treatment of tuberculosis and kidney damage in people with diabetes. The heat-processing method to strengthen the efficacy of P ginseng has been well-defined based on a long history of ethnopharmacological evidence. The protective effects of P ginseng on pathological conditions and renal damage associated with diabetic nephropathy in the animal models were markedly improved by heat-processing. The concentrations of less-polar ginsenosides (20(S)-Rg3, 20(R)-Rg3, Rg5, and Rk1) and maltol in P ginseng were significantly increased in a heat-processing temperature-dependent manner. Based on researches in animal models of diabetes, ginsenoside 20(S)-Rg3 and maltol were evaluated to have therapeutic potential against diabetic renal damage. These effects were achieved through the inhibition of inflammatory pathway activated by oxidative stress and advanced glycation endproducts. These findings indicate that ginsenoside 20(S)-Rg3 and maltol are important bioactive constituents of heat-processed ginseng in the control of pathological conditions associated with diabetic nephropathy.
Keywords: RADICAL-SCAVENGING ACTIVITY; GLYCATION END-PRODUCTS; MAILLARD REACTION; OXIDATIVE STRESS; RED GINSENG; 20(S)-GINSENOSIDE RG(3); INSULIN-RESISTANCE; FERRIC TRIMALTOL; AMERICAN GINSENG; KIDNEY-DISEASE